Stet : poems - Malech, Dora (Princeton series of contemporary poets., 2018)
A fascinating collection of serious and playful poems that tap the inventive possibilities of the anagram and other constraining formsIn Stet, poet Dora Malech takes constraint as her catalyst and subject, exploring what it means to make or break a vow, to create art out of a life in flux, to reckon with the body's bounds, and to arrive at a place where one might bear and care for another life. Tapping the inventive possibilities of constrained forms, particularly the revealing limitations of the anagram, Stet is a work of serious play that brings home the connections and intimacies of language."Stet," from the Latin for "let it stand," is a proofreading term meaning to retain or return to a previous phrasing. The uncertainty of changes made and then reconsidered haunts Stet as its poems explore what is left unsaid through erasures, redaction, and the limitations of spelling. How does one "go back" on one's word or "stand by" one's decisions? Can a life be remade or revised, or is the past forever present as in a palimpsest? Embodying the physicality and reproductive potentiality inherent in the collection's forms and figures, Stet ends expectantly, not searching for closure but awaiting the messy, living possibilities of what comes next. By turns troubling and consoling, Stet powerfully combines lyric invention and brilliant wordplay.